The role of urinary microbiota in primary and recurrent bladder cancer: insights from a propensity score matching study - Zhaoyang Sheng; Jinshan Xu; Maoyu Wang; Xi Xu; Jinpeng Zhu; Shuxiong Zeng; Chuanliang Xu; Zhensheng Zhang (BMC Cancer)
Abstract Background Bladder cancer (BCa) is a common urinary malignancy with high recurrence rates in non-muscle invasive bladder cancer (NMIBC), posing significant clinical challenges. Emerging evidence links urinary microbiota to cancer progression; however, their role in BCa recurrence remains unclear. This study aimed to explore urinary microbiota differences between primary and recurrent BCa to identify potential microbiological markers and mechanisms associated with recurrence. Methods Urine samples were collected from 170 BCa patients, including 125 with primary Bca(BCa_P) and 45 with recurrent BCa (BCa_R). All samples underwent 16 S rRNA gene sequencing, and clinical data were collected, including age, sex, body mass index (BMI), smoking history, pathological grade, and other biological characteristics. Propensity score matching (1:1 ratio, caliper = 0.02) minimized baseline differences, resulting in 39 matched pairs. Microbial diversity was analyzed using α and β diversity indices. Differential taxa were identified with Linear Discriminant Analysis Effect Size (LEfSe), and functional pathways were predicted using Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt). Results Alpha diversity was significantly higher in BCa_P than BCa_R, particularly in Chao1 indices. β diversity revealed distinct microbial structures (ADONIS, P = 0.004, R² = 0.025). At the phylum level, both BCa_P and BCa_R were dominated by Firmicutes, Proteobacteria, Bacteroidetes, and Actinobacteria, with Firmicutes significantly higher and Bacteroidetes lower in BCa_R. At the genus level, BCa_P was enriched in Sphingomonas, Corynebacterium, Capnocytophaga, Massilia, and Aquabacterium, while BCa_R showed higher levels of Aeromonas, Cupriavidus, and Bradyrhizobium. Functional predictions revealed glucose metabolism and oxidative stress pathways enriched in BCa_R, while pollutant degradation and TCA cycle pathways were prominent in BCa_P. Conclusion These findings reveal significant differences in urinary microbiota compositions and functional profiles between primary and recurrent BCa patients, with recurrent cases exhibiting reduced microbial diversity and enrichment of potentially pathogenic communities, highlighting their potential roles in tumor progression and recurrence. Trial registration Registered with the Chinese Clinical Trial Registry (ChiCTR2300070969) on April 27, 2023.